Global Analysis of General Trade and Operational Licensing - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (International Finance Corporation, Washington, D.C., 2017)
This paper examines the general purpose licensing imposed by central or local authorities, and the need to eliminate unnecessary licensing regulations imposed on businesses. This paper does not address the issue of reform of sector-specific or professional licensing regulation, but provides criteria and tools for identifying unnecessary licensing regulations, and their elimination or, in some instances, for changing licensing regulations to free notifications. Indeed, this paper argues that a simplified review of licensing regimes that identifies unnecessary licensing saves energy and resources for well-balanced reform of remaining licensing regulations, eventually providing better protection for the public at large and a more enabling business environment. This paper is primarily oriented towards reform practitioners from governments that intend to reform their business environments; development agencies; donor-funded projects; practitioners of licensing reforms; and others interested in improving state and local governance. This paper is divided into three parts: (1) overview of licensing practices that provides common definitions of licensing, analysis of justified licensing regimes with focus on criteria for their justification, and theoretical overview of unjustified and questionable licenses; (2) analysis of commonly declared functions of unjustified licenses that provides insight into the nature of these licenses and their typology; and (3) four case studies that examine how unjustified licenses can be reformed with examples of unsuccessful, partially successful, and successful reform efforts. The analytical conclusions of this paper summarize criteria for unjustified licenses; describe lessons learned from the reform efforts; and provide a practical set of recommendations to the interested parties.